Behaviour of biomass multicomponent ashes as adsorbents - Deokar, Sunil K.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Current Science, 2016)
Physico-chemical characteristics of rice husk ash and baggase fly ash, commonly referred to as biomass ashes enable their use as adsorbents. Contrary to normal expectations, it is observed that larger particles have more number, narrower and deeper pores than smaller particles. As a consequence they have higher pore volume, total surface area and hence adsorption capacity. Also, the uptake rate of adsorption depends on the silica to carbon ratio, which is seen to be smaller for larger particles and hence they take a longer time to reach equilibrium. The extent of carbon content determines the capacity, whereas silica to carbon ratio determines the kinetics of adsorption. Removal of 2,4-dichlorophenoxyacetic acid, from aqueous solution was chosen as a representative case for study and the results obtained are compared with earlier reported results.
Keywords: Adsorption capacity; bagasse; biomass ash; rice husk; silica to carbon ratio